GREENWASHING ACROSS SECTORS IN INDONESIA: HOW IT AFFECTS FIRM VALUE? - Fransisca Tharia Hartanto; John Iwan Kusno (JAT : Journal Of Accounting and Tax, 2026)
The implementation of mandatory sustainability reporting in Indonesia has raised concerns regarding greenwashing and its financial implications. This study investigates the relationship between greenwashing and firm value across sectors in Indonesia. Using Bloomberg ESG disclosure score and ESG score from 160 listed companies (475 firm-year observations) during 2022–2024, greenwashing is measured using a decoupling approach. This study uses a mean-difference test and panel data regression. The results show that sectors suspected of greenwashing behaviour exhibit significantly higher greenwashing scores than sectors without apparent greenwashing behaviour. However, greenwashing does not have a significant effect on firm value in sectors suspected of greenwashing behaviour. In contrast, greenwashing is positively associated with profitability in sectors without apparent greenwashing behaviour, although this effect is not significant when firm value is measured using PBV. These findings extend the greenwashing literature with empirical evidence from Indonesia, demonstrating that the relationship between greenwashing and firm value depends on sectoral characteristics, suggesting that the consequences of greenwashing differ across industries.